If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(c + 1) + -1(6 + 5c) = 0 Reorder the terms: -6(1 + c) + -1(6 + 5c) = 0 (1 * -6 + c * -6) + -1(6 + 5c) = 0 (-6 + -6c) + -1(6 + 5c) = 0 -6 + -6c + (6 * -1 + 5c * -1) = 0 -6 + -6c + (-6 + -5c) = 0 Reorder the terms: -6 + -6 + -6c + -5c = 0 Combine like terms: -6 + -6 = -12 -12 + -6c + -5c = 0 Combine like terms: -6c + -5c = -11c -12 + -11c = 0 Solving -12 + -11c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -11c = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -11c = 0 + 12 -11c = 0 + 12 Combine like terms: 0 + 12 = 12 -11c = 12 Divide each side by '-11'. c = -1.090909091 Simplifying c = -1.090909091
| (2x+3)+(4x+8)=180 | | =(y+6u)(7y-7u-5) | | -12x-20=-10x-15 | | -2x-10=3x-15 | | fn=5n+6 | | 16x-10+9=99-30x | | 6cosx+5=-5cosx+14 | | x+.05x=252000 | | (6x-5)(8x+3)=0 | | 187=-x+8 | | x+.05x=456 | | x+.05x=110 | | f(x)=x^3-6x^2-x+6 | | p^6-1=0 | | Y=-14x*-70x | | 2x/11 | | 3x+6x+2=-4x | | 10+10x=50+2x | | 8+w-4.7w-.5= | | 15x^2+26x+7= | | 125x^6-8=equation | | -4/9x=8 | | 5/√5xy^2 | | 5/√(5xy^2 | | 0=x^2+x-8 | | 80p^2r-245b^2r=0 | | 2v^2-10+12=0 | | 16v^4y^5-4v/4v^3x^6 | | 2r=7(r-15) | | 6m+3(2m-1)=-27 | | 5lnx-4=7 | | -9+20x=16 |